Panagontaman sa kalintad a Mindanao a framing analysis of Mindanao cross news articles about Bangsamoro Organic Law - Masbud, Ayesha Aeda A.; Comidoy, Merle Dawn S. (2019)
One of the important aspects of the Peace Process in Southern Mindanao is the Bangsamoro Organic law (BOL). It is important that the media coverage of the topic is monitored since the media act as a gatekeeper of information. Thus, this study looks into the 2018 coverage of Mindanao Cross news articles about BOL from being a proposed law yet to be implemented. This study aims to find out how Mindanao Cross frame their news articles in terms of conflict-sensitive topic and of Peace Journalism. Framing Analysis is used to determine how the Mindanao Cross frames their news articles, it uses McGoldrick and Lynch Peace Journalism as the theoretical framework. Overall, the study found out that the Mindanao Cross carefully covered the topic of BOL and they are aware of the importance of providing information to the public and their role in the Peace Process. For Peace Journalism, their framing leans forward Peace Journalism with Peace/Conflict Journalism oriented framing, the most used framing. Moreover, they frame their articles in three ideas. One peace process is important especially BOL/BBL as they are the conditions in the Peace Agreement between the government and MILF. Second conflict is a difficult period and armed conflict is not a solution. Third, BBL/BOL is the key to ending the long-lasting conflict.